If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + -1x = 72 Solving 85 + -1x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-85' to each side of the equation. 85 + -85 + -1x = 72 + -85 Combine like terms: 85 + -85 = 0 0 + -1x = 72 + -85 -1x = 72 + -85 Combine like terms: 72 + -85 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 6y+15-5y-8= | | 4n-9=8n-14 | | 7b-5= | | 16+11=-3(6x-9) | | -8t+-3t=-5t-6t | | 6m=8-24m^2 | | 6x+3x=7x+2x-3 | | -2(x-5)=26 | | 4x+1x=10x-5x+5 | | V+8=20 | | Y=10+1.6X+8X^2 | | 3x+0.5(0)=6 | | 4x+2-2x=-14 | | 6200=90.4-174000 | | -11+4n=5n-28 | | d-2=-4 | | 6(2x-x)=3 | | 4x+6+5+3=17 | | 9a+3a-4=44 | | 5x+14=-2x+30 | | 13=b+27 | | 6(x-2)-4=3x+3(-5+x) | | 3(0)+0.5y=6 | | Xsquared+6x=-8 | | -(b-1)=-2 | | 9/5(-34)+32= | | 5x-14=-2+30 | | 3x=2(125-x) | | .75x=-1 | | Y=75-5(0) | | 7(c+5)=50 | | -10=v+4 |